A new ultrasonic method for synchronous measurement of internal temperature distributions and thickness in high-temperature structures. (November 2022) - Cui, Yue; Xiang, Jing; Wei, Dong; Zhu, Liyan; Du, Yanxia; Gui, Yewei
Abstract: A new ultrasonic method for synchronous measurement of multiple parameters of heated materials is proposed in this paper. Based on the thermal-acoustic-solid coupling theory, the internal temperature distributions and thickness of solid structures are reconstructed synchronously by an alternate iterative multi-parameter identification method. Firstly, a numerical model of multi-parameter synchronous identification is obtained based on temperature dependence of the velocity of the ultrasonic wave propagating through the heated material. Then, an inverse analysis by the alternate iterative method for estimating equivalent thermal boundary conditions and thickness. In addition, experiments are carried out in order to validate the feasibility and reliability of the developed method, whose stability and accuracy are also analyzed through a comprehensive parameter analysis. The research results show that the structure thickness obtained by the alternate iteration method based on ultrasonic transit time accords with the physical reality and the internal transient temperature profiles determined ultrasonically agrees well with those obtained using thermocouples installed in the steel. It demonstrates that the method proposed in this work is an effective multi-parameter synchronous measurement means to determine the internal transient temperature distribution and thickness of high temperature structures with high accuracy by ultrasonic pulse echo measurements.